State Estimation of Material Flow Rate in a Hot Rolling Mill for Steel Bars. Issue 2 (2020) - Schaefer, Marc-Simon; Wahrburg, Juergen; Roth, Hubert
Abstract: We present a solution for the estimation of the material flow rate for a hot rolling mill for steel bars. In this mill, a high number of uncertainties influences the rolling process. The partly unmeasured flow rate is a critical state for the plant stability. A meaningful estimation increases the operator efficiency. For this, a developed and adapted model of a six-stand finishing mill is used for optimization purpose. The flow rate is estimated with an moving horizon estimator (MHE) with the help of the CasADi framework. The main contribution is the adaption of a simulation model with the usage for online state estimation. The proposed solution is linked with real plant measurements.